2021
DOI: 10.1111/bld.12379
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 restrictions in the United Kingdom on the positive behavioural support of people with an intellectual disability

Abstract: Accessible summary The way that people with an intellectual disability are supported is very important. The COVID‐19 virus has changed the way that staff help people with an intellectual disability. We wanted to know about those changes and whether learning about positive behavioural support (PBS) helped staff to cope with them. The main changes were that people with an intellectual disability could not go out or see family and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
1
16
0
2
Order By: Relevance
“…The included studies came from developed countries, four from Europe (two from the UK ( McKenzie et al, 2021 ; Murray et al, 2021 ), one from the Netherlands ( Embregts et al, 2021 ), and one from Ireland ( McMahon et al, 2020 )) and one from Canada ( Lunsky et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies came from developed countries, four from Europe (two from the UK ( McKenzie et al, 2021 ; Murray et al, 2021 ), one from the Netherlands ( Embregts et al, 2021 ), and one from Ireland ( McMahon et al, 2020 )) and one from Canada ( Lunsky et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from research studies reflect concerns similar to those expressed in clinician opinion pieces. Over a 15‐month period, several studies explored the impacts of pandemic‐related closures and restrictions on the mental health and well‐being of people with ID from numerous countries, including Chile (Rosencrans et al, 2021 ), Italy (Zingale et al, 2020 ), South Korea (Kim et al, 2021 ), United Kingdom (Courtenay, 2020 ; Courtenay & Perera, 2020 ; McKenzie et al, 2021 ; Murray et al, 2021 ; Rawlings et al, 2021 ; Willner et al, 2020 ), United States (Jeste et al, 2020 ), Canada (Lake et al, 2021 ), Ireland (McCarron et al, 2020 ; McCausland et al, 2021 ), France (Nollace et al, 2020 ), Spain (Amor et al, 2021 ; Navas, Amor, et al, 2021 ), Netherlands (Embregts et al, 2020 ; Scheffers et al, 2021 ; Schuengel et al, 2020 ; Zaagsma et al, 2020 ), and Israel (Araten‐Bergman & Shpigelman, 2021 ). To date, there has been a prominent focus on the challenges experienced by children and youth with ID and their families as a result of pandemic response plans, such as the transition of in‐person learning to virtual education.…”
Section: Methodsmentioning
confidence: 99%
“…A UK survey of ID mental health services observed increases in urgent psychiatric consultations to address a deterioration in mental health and behaviour ( Rauf et al, 2021 ), similar to increases observed by a Dutch online support service ( Zaagsma et al, 2020 ). Both observational and family-report studies reveal significant increases in challenging behaviour during lockdown ( Schuengel et al, 2020 ; Wieting et al, 2021 ) which in turn led to a negative appraisal of persons with IDD ( Murray et al, 2021 ). While the disruption to support services for persons with IDD throughout the pandemic was wide ranging, it was deemed to have a specific detrimental impact for those who engage in behaviours that challenge ( Gleason et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%